RUTILE NANORODS: SYNTHESIS, STRUCTURE AND ELECTROCHEMICAL PROPERTIES - V.O. Kotsyubynsky; I.F. Myronyuk; V.L. Chelyadyn; V.V. Moklyak (Vasyl Stefanyk Precarpathian National University, 2014)
Nanodispersed rutile with rod-like particles was synthesized by hydrolysis of TiCl4 in hydrochloric acid - ethanol alcohol aqueous solution at 40°C. It was found that the specific surface area, crystallite size, degree of agglomeration are determined by molar ratios of ethanol. The obtained material was used as the base of cathode composition for lithium power sources. The maximum values of specific capacity (250 mAh/g) at discharge in galvanostatic conditions are fixed in the case of using material with the maximum agglomeration degree and minimal particle size. Phasic character of Li+ ions intercalation is set and the diffusion coefficient at different stages of the process is calculated.